Effect of additive contents on the performances and structural Properties of Asymmetric Polyethersulfone (PES) nanofiltration membranes - Ismail, A. F.; Hassan, A. R. (Elsevier, 2007)
The effects of additive concentration polyvinylpyrrolidone (PVP K30) on the performance and morphological structure of polyethersulfone (PES) nanofiltration membranes were investigated by varying polymer concentration ranges from 1.00 to 9.00 wt%. By using the solution–diffusion mechanism and theoretical models, the structural properties of membranes were deduced. The effects and relationship between additive concentration on membrane performance and structural properties have been intensively investigated. The results showed that the addition of 1.00 wt% additive (PVP K30) into polymer solution was found to increase fluxes to about 4×10-7 m/s and decrease the salt rejection approximately by 2.34% of the resultant membranes. In addition, the same amount of additive wills also reduce an effective membrane thickness to about 2.8×10-6 m resulting in an increase of salt permeability to about 3.8×10-8 m/s. The modeling results showed that by addition of 1.00 wt% additive, the membrane’s pore radius is increased to about 0.05 nm. The electrostatics parameters such as effective charge density and membrane surface charge were found to reduce to about 0.46 mol/m3 and 0.05, respectively.